Samuel H. Clark papers - Clark, Samuel H., 1885-1979.
Chiefly documentation kept by Clark as head of the Association of Colored Railway Trainmen and Locomotive Firemen, including files (1945-1949) from the union's Norfolk and Western Railway Company Lodge No. 35 Grievance Committee. Materials include correspondence, speech, court opinion for Clark v. Norfolk and Western Railway Company, railroad rosters, clipping, and printed matter. Includes correspondence with Genna Rae McNeil and a portion of McNeil's dissertation concerning Charles Hamilton Houston and the right to work.
Labor leader and railroadman.
Collection material in English.
Keywords: Houston, Charles Hamilton, -- 1895-1950.; McNeil, Genna Rae; McNeil, Genna Rae -- Correspondence; Association of Colored Railway Trainmen and Locomotive Firemen; Norfolk and Western Railway Company; African Americans -- Employment; Labor unions, Black -- United States; Railroads -- Employees -- Labor unions; Railroads -- United States; Right to labor -- United States; Labor leaders; Railroadmen